Economy and society a new translation - Weber, Max 1864-1920 (Harvard University Press, 2019)
Introduction to Max Weber's Economy and Society -- Overview of Chapter One -- 1. Basic Sociological Concepts -- Overview of Chapter Two -- 2. Basic Sociological Categories of Economic Action -- Overview of Chapter Three -- 3. Types of Rule -- Overview of Chapter Four -- 4. Social Ranks and Social Classes -- Appendix A: Translation Appendix -- Appendix B: The Definitional Paragraphs of Chapter 1 -- Acknowledgements -- Index.